Investigation of Mechanical Behavior of Barrel after Geometric Changes on the Mortar - Pihtili, Hasim; Ulutas, Melih (Defence Scientific Information Documentation Centre, 2023)
The area close to the firing part as of the muzzle of a 120 mm mortar consists of trapezoidal threads. In order for the 120 mm mortar to hit the target, the target is aimed by giving the required angle with the help of these trapezoidal screw threads. Since it takes a lot of time to set the target in this way, the aim is to develop a hydraulic mechanism that automatically gives an angle to the system by lifting the trapezoidal screw threads instead of mechanically setting the angle to be adjusted easily in the shortest time. Thus, it is intended to convert the mortar into a full-automatic system that can rotate 360 degrees around itself and can be adjusted to the desired angle in a short time and very precisely. The present study is conducted in two steps. At first, thermo-mechanical analyses for the stresses affecting during firing of the currently used 120 mm mortar with a screw thread were investigated by ANSYS Workbench finite elements method. Then, the status of the mortar after removing the screw threads was examined in the ANSYS Workbench program under the effect of the same stresses and the results were compared between the two mortars and it was examined whether it is safe to remove the screw threads. When the analyses were examined, the temperature distribution was higher in the barrel without screw threads as a result of the first thermal analysis. When the analyses were examined in terms of statics, it was observed that it was high in the mortar barrel without screw threads
Keywords: Mortar; Mortar barrel; Barrel; Interior ballistic